VD_FINDINFO HC / 2016 / 550 vom 27. Mai 2016 - VD Tribunal cantonal (2016)
VISITE, ENFANT, EXPERTISE PSYCHIATRIQUE, SURVEILLANCEEN GÉNÉRAL, AUDITION DE L'ENFANT | 273 al. 1 CC, 274 al. 2 CC, 298 al. 1 CPC (CH)